Abdominal Pain as the Initial and Sole Clinical Presenting Feature of Systemic Lupus Erythematosus - Henry V Chung; Alnoor Ramji; Jennifer E Davis; Sylvia Chang; Graham D Reid; Baljinder Salh; Hugh J Freeman; Eric M Yoshida (Canadian Journal of Gastroenterology)
Classically, a diagnosis of systemic lupus erythematosus (SLE) is dependent on renal, rheumatological, cutaneous and neurological target organ damage with supporting serological markers. A previously healthy 26-year-old Japanese woman whose only manifestation of otherwise occult SLE was severe abdominal pain is reported. A computed tomographic scan of the abdomen revealed thickened loops of small bowel, endoscopic findings were nonspecific and jejunal biopsy revealed a nonspecific enteritis. Laboratory studies revealed lymphopenia, hypocomplementemia, a positive antinuclear antibody, a weakly positive anti-Smith and a strongly positive anti-double stranded DNA. There was a prompt symptomatic recovery with immunosuppressive therapy. The authors’ experiences, and a review of the literature suggest that a diagnosis of SLE should be considered in young Asian women who present with significant but clinically enigmatic gastrointestinal illness.